Uji Parameter Kimia Air Sumur Gali di Desa Pagerwojo, Buduran, Kabupaten Sidoarjo - Rizqi Widi Rahmadani; Rr. Diah Nugraheni Setyowati; Widya Nilandita (Jurnal Ekologi, Masyarakat dan Sains, 2022)
The people of Pagerwojo Village use well water for their daily needs. Well water that is used often produces an unpleasant odor and leaves a yellow-brown precipitate. This research was conducted with the aim of knowing the concentration of the chemical parameters manganese, iron, pH, and hardness in well water belonging to the surrounding community. The research method uses a quantitative descriptive approach. The number of sampling points for testing well water is 6 points in each hamlet with consideration of purposive sampling of dug wells adjacent to the pollutant source. The results of the well water quality test found that the concentration of manganese parameters in sample A was 1.74 mg/l and sample F was 0.90 mg/l. Manganese concentration that exceeds the water quality standard threshold of 0.5 mg/l sanitation hygiene PMK No. 32 of 2017 causes yellow-brown colored deposits and causes an unpleasant odor in well water.